Quality retention of microwave dried pineapple peels and core / Nurul Asyikin Md Zaki and Siti Fabilah Ismail - Md Zaki, Nurul Asyikin; Ismail, Siti Fabilah (Universiti Teknologi MARA Shah Alam, 2018)
Pineapple wastes such as peels and core contain many nutritional values and can be utilised for many purposes. Thus, this work aims to study the drying characteristics and quality of pineapple peels and core in microwave drying. The pineapple peels and core were dried under different microwave power (180 W, 450 W, and 850 W). The total phenolic content (expressed as gallic acid equivalent GAE) and antioxidant activity of microwave dried peels and core were analysed. The findings show higher microwave power led to shorter drying time, thus resulting to high drying rate. For the quality analysis, dried peels and core retained significant amount of total phenolic content. Dried peels and core had 19.8 mg GAE/g dry sample and 21.3 mg GAE/g dry sample, for drying at power level of 180 W and 800 W, respectively. Furthermore, dried peels and core were also found to retain significant antioxidant activity. Dried pineapple core at 180 W achieved around 74% DPPH inhibition which shows high antioxidant activity was still available. In conclusion, microwave drying retains significant quality of dried pineapple peels and core and has potential as alternative for preservation of fruits.